(untitled) (Stamford Journal of Microbiology, 2017)
The present study was carried out to assess the degree of microbiological proliferation in tannery wastes and the surrounding environment of the tannery industries. In this regard, a total of 8 tannery waste (n=4) and environmental (n=4) samples were tested. All the samples contained a huge load of bacteria and fungi in an average of 108 cfu/g or ml. An extended numbers of pathogenic bacteria were recovered. Among the pathogenic bacteria, Staphylococcus spp. was predominant. Most of the samples exhibited the presence of Pseudomonas spp. Salmonella spp. and fecal coliform were found each in one sample. Bacillus spp., Escherichia coli, Klebsiella spp. and Vibrio spp. were found in few samples. The average load of the pathogens was 104 cfu/g or ml. All the pathogenic isolates were found to be multidrug resistant. Higher resistance was found against penicillin and streptomycin. Tannery waste after lather treatment sample showed antibacterial activity against all the pathogens tested. Overall, presence of pathogenic microorganisms with multidrug resistance traits may pose serious public health threats. Stamford Journal of Microbiology, Vol.7(1) 2017: 14-18